In vivo odourant response properties of migrating adult-born neurons in the mouse olfactory bulb - Kovalchuk, Yury; Homma, Ryota; Liang, Yajie; Maslyukov, Anatoliy; Hermes, Marina; Thestrup, Thomas; Griesbeck, Oliver; Ninkovic, Jovica; Cohen, Lawrence B.; Garaschuk, Olga (NATURE PUBLISHING GROUP, 2015)
Juxtaglomerular neurons (JGNs) of the mammalian olfactory bulb are generated throughout life. Their integration into the preexisting neural network, their differentiation and survival therein depend on sensory activity, but when and how these adult-born cells acquire responsiveness to sensory stimuli remains unknown. In vivo two-photon imaging of retrovirally labelled adult-born JGNs reveals that similar to 90% of the cells arrive at the glomerular layer after day post injection (DPI) 7. After arrival, adult-born JGNs are still migrating, but at DPI 9, 52% of them have odour-evoked Ca2+ signals. Their odourant sensitivity closely resembles that of the parent glomerulus and surrounding JGNs, and their spontaneous and odour-evoked spiking is similar to that of their resident neighbours. Our data reveal a remarkably rapid functional integration of adult-born cells into the preexisting neural network. The mature pattern of odour-evoked responses of these cells strongly contrasts with their molecular phenotype, which is typical of immature, migrating neuroblasts.
Keywords: GRANULE CELLS; LONG-TERM; SYNAPTIC INTEGRATION; GENERATED NEURONS; NEWBORN NEURONS; CRITICAL PERIOD; SENSORY INPUT; NEUROGENESIS; SURVIVAL; INTERNEURONS